2006
DOI: 10.1016/j.febslet.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids 15–28 in the ectodomain of SARS coronavirus 3a protein induces neutralizing antibodies

Abstract: A synthetic peptide corresponding to amino acids (aa) 15-28 of the severe acute respiratory syndrome coronavirus (SARS-CoV) 3a protein was used to raise polyclonal antibodies in rabbits. This anti-3a N-terminal antibody could detect 3a protein in infected cells, as did an anti-3a C-terminal antibody previously described. The latter targeted the C-terminal cytoplasmic domain of 3a (aa 134-274). The anti-3a N-terminal antibody could detect intracellular 3a as well as 3a expressed on the cell surface. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Of all the surface proteins, only the ectodomains of S (spike) and Orf3a can induce significant neutralizing antibody with some augmentation from the M (matrix) and E (envelope) proteins. 41,42 Though Orf3a is absent in HCoV-EMC, we cannot completely exclude the possibility that similar Orf3a-like proteins are being coded by the accessory protein gene but homology search does not reveal the presence of similar protein. All betacoronaviruses use the S protein for attachment and fusion of the virion with the host cell membrane.…”
Section: Discussionmentioning
confidence: 89%
“…Of all the surface proteins, only the ectodomains of S (spike) and Orf3a can induce significant neutralizing antibody with some augmentation from the M (matrix) and E (envelope) proteins. 41,42 Though Orf3a is absent in HCoV-EMC, we cannot completely exclude the possibility that similar Orf3a-like proteins are being coded by the accessory protein gene but homology search does not reveal the presence of similar protein. All betacoronaviruses use the S protein for attachment and fusion of the virion with the host cell membrane.…”
Section: Discussionmentioning
confidence: 89%
“…The sera from rabbits immunized with recombinant ORF3a (a.a. 125–274) does not exhibit any significant neutralizing activity on SARS-CoV infected Vero E6 cells [59]. In another study, however, sera from rabbits immunized with a different recombinant ORF3a (a.a. 15–28) contains neutralizing antibodies that do inhibit SARS-CoV infection in Vero E6 cells [61]. These contrasting results could be explained by differences in the immunogenicity of the central region and C-terminal domain compared to the N-terminal ectodomain, respectively.…”
Section: Sars Accessory Proteinsmentioning
confidence: 99%
“…In addition, it was recently reported that the N-terminal domain of 3a protein elicits strong and potentially protective humoral responses in infected patients (Zhong et al, 2006). Accordingly, rabbit polyclonal antibodies raised against a synthetic peptide corresponding to aa 15-28 of 3a protein inhibit SARS-CoV propagation in Vero E6 cells, in contrast to antibodies specific for the C-terminal domain of the protein (Akerstrom et al, 2006). SARS-CoV E, M, and 7a proteins have shown low immunogenicity (Tan et al, 2004a).…”
Section: Antigens Involved In the Protection Against Cov Induced Infementioning
confidence: 99%